TRANSFORMING PESANTREN ADOLESCENTS INTO ANTI-BULLYING AGENTS THROUGH THE BULLY BLOCKING PROGRAM: TRANSFORMASI REMAJA PESANTREN SEBAGAI AGEN ANTI-BULLYING DENGAN PROGRAM BULLY BLOCKING - Yuhbaba, Zidni Nuris; Suswati, Wahyi Sholehah Erdah (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Bullying is a significant issue affecting adolescents in both schools and islamic boarding schools (pesantren). It has detrimental effects on academic performance, social skills, and mental health for both bullies and victims. The